All that is [compact disc, unabridged] : a novel - Salter, James (Blackstone Audio, 2013)
After his experiences as a young naval officer in battles off Okinawa, Philip Bowman returns to America and finds a position as a book editor. Bowman finds he fits in perfectly. But despite his success, love eludes him. His first marriage goes bad, another fails to happen, and finally he meets a woman who enthralls him and sets him on a course he could never have imagined for himself.